Internalizing Tarbawi Hadith Values Through Father Involvement: Strengthening Children’s Character Formation and Learning Motivation in Islamic Education - Usep Malik Haerudin; Anidah Inayah (AL-ADABIYAH: Jurnal Pendidikan Agama Islam, 2026)
This study examines the internalization of tarbawi hadith values through father involvement in strengthening children’s character formation and learning motivation within Islamic education. The purpose of this study is to analyze how fathers implement prophetic educational values in family-based education through their roles as role models, motivators, spiritual guides, supervisors, and protectors. This study also seeks to explore the relevance of father involvement in addressing contemporary moral and educational challenges among children in the digital era. This research employed a qualitative approach using the library research method. Data were collected from the Qur’an, tarbawi hadiths, classical Islamic educational literature, scientific journal articles, books, and other relevant academic sources discussing Islamic parenting, father involvement, character education, and learning motivation. The collected data were analyzed using descriptive qualitative analysis and thematic content analysis to identify conceptual relationships between prophetic educational values and paternal educational practices. The findings reveal that father involvement has a significant influence on children’s moral, spiritual, emotional, and academic development. Fathers who consistently demonstrate exemplary conduct, emotional support, spiritual guidance, and compassionate supervision contribute positively to children’s character formation, self-confidence, discipline, religious awareness, and learning motivation. The study further indicates that educational methods rooted in tarbawi hadith values (habituation, dialogue, appreciation, and role modeling) are effective in internalizing Islamic values within children’s daily lives. The novelty of this study lies in its integration of prophetic educational values derived from tarbawi hadiths with contemporary discussions on father engagement and Islamic parenting. This study contributes theoretically to the discourse of Islamic education by reconstructing fatherhood as a transformative educational practice grounded in spiritual, moral, and emotional dimensions within contemporary Muslim families.